Hidden Efficiencies. Issue 4 (January 2015) - Ciarametaro, Mike; Bradshaw, Steven E.; Guiglotto, Jillian; Hahn, Beth; Meier, Genevieve; Dessein., Rodrigue
<x xml:space="preserve">Abstract</x> Abstract The objective of this work is to demonstrate the potential time and labor savings that may result from increased use of combination vaccinations. The study (GSK study identifier: HO-12-4735) was a model developed to evaluate the efficiency of the pediatric vaccine schedule, using time and motion studies. The model considered vaccination time and the associated labor costs, but vaccination acquisition costs were not considered. We also did not consider any efficacy or safety differences between formulations. The model inputs were supported by a targeted literature review. The reference year for the model was 2012. The most efficient vaccination program using currently available vaccines was predicted to reduce costs through a combination of fewer injections (62%) and less time per vaccination (38%). The most versus the least efficient vaccine program was predicted to result in a 47% reduction in vaccination time and a 42% reduction in labor and supply costs. The estimated administration cost saving with the most versus the least efficient program was estimated to be nearly US $45 million. If hypothetical 6- or 7-valent vaccines are developed using the already most efficient schedule by adding additional antigens (pneumococcal conjugate vaccine and Haemophilus influenzae type b) to the most efficient 5-valent vaccine, the savings are predicted to be even greater. Combination vaccinations reduce the time burden of the childhood immunization schedule and could create the potential to improve vaccination uptake and compliance as a result of fewer required injections.